A clinical and biological evaluation of a novel, noninvasive radiofrequency device for the long‐term reduction of adipose tissue. Issue 2 (February 2014) - Boisnic, Sylvie; Divaris, Marc; Nelson, Andrew A.; Gharavi, Nima M.; Lask, Gary P.
<x xml:space="preserve">Abstract</x> Background and Objective A novel, noninvasive technology, utilizing suction‐coupled radiofrequency (RF) heating and ultra‐short pulse duration, high‐voltage electrical pulses was studied for its efficacy and safety on adipose tissue reduction. Methods Twenty‐one subjects underwent treatment of their abdominal fat once weekly for 6 weeks. Clinical outcomes including abdominal circumference, adipose tissue thickness (measured by ultrasound), adipose tissue weight, body weight, and clinical photographs were obtained at visits 1 and 3 months after last treatment. Adverse events were recorded. Three subjects, who were undergoing a future elective abdominoplasty, were treated with the same protocol, but on only one side of the abdomen before abdominoplasty. Biopsies from the RF‐treated and untreated sides were harvested during abdominoplasty and cultured; measurements of adipocyte size and shape, rate of apoptosis, collagen production, and dermal thickness were determined. Results Significant clinical improvements (P < 0.05) were observed for the following clinical outcomes: reduction of abdominal circumference (113.4–110.7 cm), reduction of subcutaneous adipose tissue thickness (40.5–38.5 mm), and reduction in adipose tissue weight (32.2–30.7 kg) at 3‐month follow‐up visits. Overall patient weight also decreased, which was statistically significant at 1‐month follow‐up, but was not statistically significant at 3‐month follow‐up (73.9–73.3 kg, P = 0.609). Histologically, adipocytes were observed to have decreased size and withered shape, with increased levels of apoptosis; increased collagen synthesis, with compaction and reorganization of the dermis was also observed. Only minor, transient side effects were reported. Conclusions This novel, noninvasive RF device was effective for improving subcutaneous fat, reducing abdominal circumference and reducing subcutaneous fat layer thickness. Histologically, these improvements appear to be partly related to increased adipocyte apoptosis. Lasers Surg. Lasers Surg. Med. 46:94–103, 2014. © 2014 Wiley Periodicals, Inc.